Reference values for spirometric variables for allegedly healthy workers (2018)
Introduction: Spirometry in workers exposed to air pollutants allows for early identification of lung function impairment. Reference values (RV) for spirometric variables (SV) obtained in Cuban workers (CW) are not available.Objective: To obtain adequate SV-specific RV adequate for supposedly healthy CW.Materials and methods: Retrospective, analytical study. Forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), FEV1/FVC ratio and 25-75% forced expiration fraction for FVC (FEF25-75) values were observed in 1 088 allegedly healthy, non-smoker workers from both sexes, aged between 20 - 65 years, assisted at the Instituto Nacional de la Salud de los Trabajadores (INSAT) in Havana (Cuba) between 2009 and 2015. RV were obtained for each sex as solutions of the regression function (RF) Y=α+β x age+χ x height+ε (Y: FVC, FSV1, FEV1/FVC, FEF25-75).Results: Advanced ages were associated with lower FVC and FEV1. Taller individuals showed higher FVC and FEV1. A RF including age and height implied a higher coefficient of determination r2 and lower estimation of ε error. Behavior of SV values predicted with the locally developed equation was less biased than those obtained with other foreign equations.Conclusions: Locally developed RV may be more effective for diagnosing lung diseases in CW.